## Trending News

Promoted

### 1 Answer

Relevance

- AlanLv 74 weeks ago
call the blank square y

then, you have

6x -y = -23

2x + 5y = -13

take first equation

6x -y = -23

add y to both sides

6x = -23 + y

add 23 to both sides

y = 6x + 23

2x + 5y = -13

substitute "6x + 23" for y

2x + 5(6x+23) = -13

2x + 30x + 115 =-13

32x = -13 -115

32x = -128

x = -128/32 = -4

now substitute "-4" for x

y = 6(-4) + 23 = -24 +23 = -1

so x = -4

y = blank square = -1

Still have questions? Get your answers by asking now.